PERJUANGAN MERAIH SUPERIORITAS INDIVIDU TOKOH DALAM NOVEL KOKOKAN MENCARI ARUMBAWANGI KARYA CYNTHA HARIADI - Salsabila Tsany Naqiyyah; Chafit Ulya (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This study aims to describe the forms of struggle to achieve individual superiority in the novel Kokokan Mencari Arumbawangi by Cyntha Hariadi based on Alfred Adler's individual psychology theory. This study uses a qualitative method with a literary psychology approach that utilizes Alfred Adler's theory. The research data are in the form of quotations containing aspects of individual superiority in the novel Kokokan Mencari Arumbawangi collected through reading and note-taking techniques. The analysis techniques used include data condensation, data presentation, and drawing conclusions. The results of the study indicate that the characters in the novel experience feelings of inferiority or low self-esteem influenced by various complex social pressures. These feelings of inferiority encourage the emergence of various forms of compensation to overcome self-limitations. In addition, the characters in the novel show a drive to achieve individual superiority to maintain something they have. The findings of this study indicate that the drive for individual superiority in the novel Kokokan Mencari Arumbawangi by Cyntha Hariadi is represented through four aspects, namely optimism, independence, fighting spirit, and self-compensation. These four aspects show that the characters in the novel constantly strive to overcome obstacles and inferiority through various efforts.